Studies on Jackfruit–Okra Mucilage-Based Curcumin Mucoadhesive Tablet for Colon Targeted Delivery - Kurra, Pallavi; Narra, Kishore; Orfali, Raha; Puttugunta, Srinivasa Babu; Khan, Shah Alam; Meenakshi, Dhanalekshmi Unnikrishnan; Francis, Arul Prakash; Asdaq, Syed Mohammed Basheeruddin; Imran, Mohd. (Frontiers in Pharmacology, 2022)
The present work investigates a blend of jack fruit mucilage (JFM) and okra mucilage (OKM) as promising mucoadhesive carriers for colon-specific delivery of a curcumin (CMN)-loaded mucoadhesive tablet (CMT) formulation. Formulation optimization was performed using central composite design (CCD) to further decipher the effect of varying proportions of the mucoadhesive carriers JFM and OKG on response factors such as drug release (% DR) and mucoadhesive strength (MA). The optimized formulation CMT (F14) demonstrated a favorable 54.35% in vitro release of CMN in 12 h with release kinetics resulting from a zero-order anomalous diffusion mechanism and MA of 34.1733 ± 1.26 g. Accelerated stability testing of CMT (F14) confirmed a shelf life of about 4.7 years. In vivo drug targeting studies performed using rabbit models in order to observe transit behavior (colon-specific delivery) of the dosage form were assessed by fluoroscopic images of the GI tract. Taking the results together, the results confirm that the combination of JFM and OKM could be exploited as an ideal mucoadhesive carrier for effective delivery of macromolecules to the colon.